Pain behaviour, locomotor activity, inflammation and muscle metabolic dysregulation in pre-clinical animal models of OA and RA and the impact of PPARɣ agonism intervention - Casanova, Nuria (2019)
Background: Osteoarthritis (OA) and rheumatoid arthritis (RA) are degenerative joint diseases accompanied by pain and inflammation, which can lead to a sedentary lifestyle. Skeletal muscle inflammation and inactivity can lead to increased muscle insulin resistance and atrophy, which are associated with the dysregulation of muscle carbohydrate metabolism and changes in the expression of genes and proteins known to regulate muscle mass. This study aimed to identify the impact of OA and RA on pain behaviour, locomotor activity, inflammation and muscle metabolic dysregulation and atrophy in two animal models and the effects of the PPARɣ agonist (rosiglitazone) on these study end-points. Additionally, muscle mRNA isolated from RA patients was used to identify potential commonality of muscle gene expression between clinical and pre-clinical RA. The hypothesis of the thesis was that joint inflammation in arthritis will impact behavioural pain and activity, and skeletal muscle function.